Investigating public understanding and actions regarding Aedes mosquitoes and dengue prevention across altitudinal range in central Nepal - Punya Ram Sukupayo; Ram Chandra Poudel; Tirth Raj Ghimire (Journal of Vector Borne Diseases, 2024)
Backgrounds & objectives: Dengue fever, transmitted by Aedes mosquitoes, is a significant public health concern in Nepal. An extensive Knowledge, Attitude, and Practice (KAP) survey related to Aedes mosquitoes and prevention of dengue was conducted along the route from Matihani (62 m above sea level) to Kalinchok (3840 m asl) in central Nepal. This research examined residents’ awareness of Aedes mosquitoes and the diseases they transmit, aiming to support the World Health Organization’s national and global fight against mosquito-borne diseases. Methods: The survey included 550 participants aged 18-75 years (249 males and 201 females). Door-to-door campaigns were conducted to gather data on knowledge scores, practices, and attitudes about Aedes mosquitoes using a standard structured questionnaire. Results: Findings of this study revealed a moderate level of knowledge across the study area, with a mean knowledge score of 5.525±2.58 (correct answer rate of 46.05%). While 99.6% of respondents were aware of dengue transmission by mosquitoes, only 64.5% were able to report Aedes mosquitoes as the key transmitter. Less than one-third of the participants (27.8%) were familiar with black-and-white stripes in Aedes. Additionally, only 36.7% were knowledgeable about the day-biting behavior of Aedes mosquitoes. Interpretation & conclusion: This KAP survey provides valuable insights into community understanding of Aedes mosquitoes and dengue prevention practices associated with various Nepalese communities residing in low to high altitudes of central Nepal. These findings can be adopted to address the increasing health burden faced by countries with low-to-high altitude regions within the Hindu Kush Himalayas.